Geographical and cultural proximity in retail banking - Santiago Carbó Valverde; Hector Perez-Saiz; Hongyu Xiao (Bank of Canada, 2023)
This paper measures how both geographical and cultural proximity of bank branches affect household credit choice and pricing. We examine both types of proximity jointly to separately identify the importance of soft information versus alternative mechanisms. Using a detailed household-level database for Canada, we find that both geographical and cultural proximity increase consumer credit by reducing the cost of obtaining soft information. Furthermore, soft information obtained via the two types of proximity can be either substitutes for or complements to each other, with complementarity being more likely for products that require high levels of ex-ante screening. Overall, our results suggest that ongoing branch consolidation, happening in many countries, may lead to lower financial inclusion, especially in culturally diverse neighbourhoods.
Keywords: D82; D83; G20; G21; R22; Z10; Z13; 330; Credit and credit aggregates; Financial institutions; Financial services